Sustainable Earnings Dynamics: An Analysis of Influential Factors on Earnings Quality in The Transportation Sector of The Indonesia Stock Exchange - Ghassany, Amalia; Aurelia, Sopie; Sujarminto, Aditya; Kaya, Putu Bagus Tutuan Aris (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This research investigates the impact of firm size, foreign ownership, inflation, profit growth, and the Indonesia Country Risk Premium on the Earnings quality of transportation sector firms listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. The study employed a purposive sampling method, selecting 84 firms that met the established criteria for analysis. Using multiple linear regression, the findings reveal that firm size, foreign ownership, inflation, and profit growth significantly influence Earnings quality, with larger firms and those with higher foreign ownership demonstrating better Earnings quality. Contrary to expectations, inflation was positively correlated with Earnings quality, possibly reflecting sector-specific dynamics in Indonesia. Additionally, profit growth was found to have a positive effect on Earnings quality, emphasizing the importance of growth strategies for enhancing financial performance. However, the Indonesia Country Risk Premium was not found to have a statistically significant impact on Earnings quality, suggesting that external country risk factors were not key determinants during the study period. These results indicate that transportation companies should prioritize optimizing internal factors such as firm size and profit growth, while also carefully managing external factors like inflation and foreign ownership in their strategic planning. Despite the non-significant role of the Indonesia Country Risk Premium, it is still important for firms to stay vigilant regarding potential macroeconomic risks. The study further highlights the value of investing in sustainable infrastructure to improve operational efficiency and long-term resilience. By incorporating these insights, transportation companies on the IDX can better position themselves to remain adaptive and competitive in an ever-changing economic environment.